Photoemission electron microscopy for connectomics - Gregg Wildenberg; Kevin M. Boergens; Lola Lambert; Ruiyu Li; Allison Craig; Michael K. L. Man; Amin Moradi; Janek Rieger; Hengli Duan; Sarnjeet S. Dhesi; Gabriel Karras; Francesco Maccherozzi; et al. (Proceedings of the National Academy of Sciences, 2025)
Photoemission electron microscopy (PEEM) offers a potential third modality for large-volume connectomics alongside transmission electron microscopy (TEM) and scanning electron microscopy (SEM). We image osmium stained, ultrathin brain sections on gold coated silicon at synaptic resolution using commercial PEEMs. At coarser resolution, we demonstrate that ultraviolet laser illumination enables gigavoxel-per-second acquisition rates without thermal damage. PEEM combines TEM-like parallel detection with SEM-compatible solid supports into a potentially scalable and cost-effective approach for large-volume connectomes.